The Effect of Risk on the CEO Market - Edmans, Alex; Gabaix, Xavier (Review of Financial Studies, 2011)
This article presents a market equilibrium model of CEO assignment, pay, and incentives under risk aversion and moral hazard. Each of the three outcomes can be summarized by a single closed-form equation. In the presence of moral hazard, assignment is distorted from positive assortative matching on firm size as firms with higher risk or disutility choose less talented CEOs. Such firms also pay higher salaries in the cross-section, but economywide increases in risk or the disutility of being a CEO do not affect pay. The strength of incentives depends only on the disutility of effort and is independent of risk and risk aversion. If the CEO can affect firm risk, incentives rise and are increasing in risk and risk aversion. We calibrate the losses from various forms of poor corporate governance, such as failures in monitoring and inefficiencies in CEO assignment. (JEL G34, J33) This article presents a market equilibrium model of CEO assignment, pay, and incentives. Risk-averse managers of different talents are hired in a competitive market by heterogeneous firms, which vary in their size, risk, and level of effort required. The level of pay drives the assignment of talent to firms. The strength of incentives induces the efficient effort level, and is determined by an optimal